THE EFFECT OF PREGNANCY EXERCISE ON SLEEP QUALITY THIRD TRIMESTER PREGNANT WOMEN IN HEALTH COMMUNITY CENTER PAYUNG SEKAKI PEKANBARU 2019 - Faradilla, Lidia; Helina, Siska; Hevrialni, Rully (JURNAL IBU DAN ANAK, 2020)
Abstract Fisiology anatomy change in the pregnant women make a complaints that oftenappear one which is sleep disorder. 50% of third trimester pregnant womens inPayung Sekaki Health Community Center experience sleep disorder. One way toovercome is with pregnancy exercise. The research aim is for knowing the effect ofpregnancy exercise on sleep quality in third trimester pregnant women in HealthCommunity Center Payung Sekaki Pekanbaru on March until June 2019. Theresearch used pre experiment with one group pretest and post test design.Populations this research is all pregnant women in the third trimester at PayungSekakiPekanbaru Health Community Center and samples this research was 29 peopletaken by purposive sampling technique. Data the sleep quality in research usePittsburgh Sleep Quality Index (PSQI) questionnaire. Univariate and bivariate dataanalysis using the Wilcoxon test. Result the research show there is increase sleepquality in third trimester pregnant women with p value 0,000 (p<0,005) that meansthere is significant effect ofsleep quality in third trimester pregnant women beforeand after pregnancy exercise.Suggestions in this study are that the research siteconducts a pregnancy exercise program an invites pregnant women to take part inpregnancy exercises regularly.